Molecular survey of vector-borne agents in lowland tapirs (Tapirus terrestris) from Brazil reveals a new Anaplasma genotype - Mongruel, Anna Claudia Baumel [UNESP]; Medici, Emília Patrícia; Canena, Ariel Costa; Cordova, Amir Salvador Alabi [UNESP]; Freitas das Neves, Lorena [UNESP]; Franco, Eliz de Oliveira [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Elsevier, 2024)
Although vector-borne agents have been detected in different species of wild animals, studies involving tapirs (Tapirus terrestris), the largest land mammals in Brazil, are scarce. The aim of the present study was to investigate the occurrence and molecular identity of Anaplasmataceae agents, Coxiella burnetii and Hepatozoon spp. in blood samples of wild T. terrestris from two biomes (Cerrado and Pantanal) in Brazil. A total of 122 blood samples from 99 tapirs were analyzed. Sixty-one tapirs were sampled in Pantanal, whereas 38 were from Cerrado biome. DNA was extracted from blood samples and subjected to conventional and/or quantitative PCR assays for molecular screening and characterization of DNA from Anaplasmataceae agents (Anaplasma, Ehrlichia, and Neorickettsia), C. burnetii and Hepatozoon spp. None of the samples were positive for Ehrlichia, C. burnetii or Hepatozoon spp. Twenty-two samples (22/122; 18%) amplified fragments from the expected size for the Anaplasma 16S rRNA fragment tested herein. Out of these samples, 2 (9.1%) presented amplification for the Anaplasma ITS 23S-5S. Nine positive samples for the 16S rRNA assay were selected for cloning and sequencing. Phylogenetically, distance and haplotype analyses based on large fragments (>1,200 bp) of the 16S rRNA suggest that tapir-related Anaplasma and Anaplasma odocoilei are genetically similar species. Moreover, 31 (25.4%) samples were positive for Neorickettsia based on amplification of partial 16S rRNA. Phylogenetic assessment of the three obtained sequences demonstrated relatedness to Neorickettsia risticii, the causative of Potomac fever in horses. This is the first report of Neorickettsia sp. and description of a new Anaplasma genotype in tapirs.
Keywords: Anaplasmataceae; Hemoparasites; South America; Tick-borne diseases; Wildlife